Influence of low length-to-diameter ratio and nozzle pressure ratio in an abruptly expanded flow - Khan, Sher Afghan (2015)
This paper presents an investigation on the efficiency of micro jets to manage the base pressure in rapidly expanded axi-symmetric duct. Four tiny jets of 1mm orifice diameter located at 90 intervals along a pitch circle diameter of 1.3 times the nozzle outlet diameter in the base region were employed as controls. The Mach numbers of the abruptly expanded flows were 1.25, 1.3, 1.48, 1.6, 1.8, 2.0, 2.5 and 3.0. The jets were expanded suddenly into an axi-symmetric circular brass tube with cross-sectional area 2.56, 3.24, 4.84 and 6.25 times that of the nozzle exit area. The Length to Diameter ratio of the suddenly expanded tube was varied from 10 to 1 and Nozzle Pressure Ratio was varied from 3 to 11. However, the results presented were for Low Length to Diameter ratio equal to 4; since when the flow was discharged to the ducts of the above area ratio it remained attached with the duct wall for all the Mach numbers and the NPRs tested in the present case. It was found that the level of expansion plays a significant role to decide on the value of the base pressure and the control effectiveness. Whenever, the flow is over expanded, an oblique shock will be formed at the nozzle lip, which in turn will result in increase of the base pressure. The formation of the shock waves, reflection and recombination will continue till the pressure becomes atmospheric. It was observed that the flow remains attached even for low length-to-diameter ratio is equal to 4. No adverse effect of back pressure was observed during the test. It was found that the micro jets can serve as controllers for the base pressure. Also, the micro jets do not adversely influence the wall pressure variation.